Factors Influencing Recovery among Children with Moderate Acute Malnutrition Treated at Kirehe District Health Centers - Bihibindi Kabundi, Vianney; Kayihura, Camille; Marete, Onesmus; Habarurema, Nicodeme; Rutayisire, Erigene (Journal of Public Health International, 2020)
Acute malnutrition affects nearly 52 million of under five years children globally, 75% of them live in low to middle income countries. The treatment of acute malnutrition using supplement foods could help children recovering and could reduce the risk of sickness. The present study investigated the factors associated with recovery among children with moderate acute malnutrition (MAM) under a follow-up program at health facilities. A prospective study was conducted in 16 health centers of Kirehe District of Rwanda and included 200 children from 6 to 59 months. A semi-structured questionnaire was used for data collection. All children enrolled in the study spent three months in nutrition program at health centers. The results show that after 3 months in the program 77.5% recovered from MAM. Children aged above 36 to 59 months were recovered at 90% whereas children aged from 24-35 months were recovered at 73.5%. Micronutrients and deworming provided at health facility were contributed to the recovery as children who received them were recovered at 89.1% and for those who didn’t were recovery at 72.1%. The findings demonstrated that boys were 16 times more likely to recover from MAM in three months of intervention than girls (AOR=16.19, p<0.001, 95% CI: 5.39- 48.63). Children from moderate income families were 3 more likely to recover than those from very low income families (AOR=2.8, p=0.029, 95% CI: 1.11-7.51). Male gender, receiving micronutrients and deworming from health facilities and family income status were factors associated with MAM recovery status
Keywords: Malnutrition; recovery; moderate acute malnutrition; Kirehe District